Primary intrapulmonary thymoma a case report - Sheikh Muhammad Wasim Jamal; Mousa Hussein; Mutaz Albakri; Ibrahim Rasheed; Mansoor Hameed; Irfan Ul Haq; Merlin Thomas; Issam Al Bozom; Hisham Abdul Sattar (Clinical Case Reports, 2023)
Abstract Primary intrapulmonary thymoma (PIT), defined as the presence of thymoma tissue in the lung without an accompanying mediastinal component, is uncommon and so offers a diagnostic quandary. We describe the case of PIT in an 81‐year‐old man.